EKSAMINASI KLAIM SANAD BERSAMBUNG DALAM PENYEBARAN HADIS DI MEDIA SOSIAL PERSPEKTIF TAHAMMUL WAL ADA’ - Arofatul Muawanah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study examines the examination of claims of connected sanad (chain of transmission) in the dissemination of hadith on social media through the lens of tahammul wa Ada’ul hadis(the reception and transmission of hadith). Social media has become a popular medium for religious transmission, including the dissemination of hadith, but the sanad claims often lack adequate verification. This research aims to analyze the validity of such claims by referring to the principles of tahammul (receiving) and ada’ (transmitting) hadith in the tradition of hadith scholarship. The research method employed is qualitative, using a descriptive-critical analysis approach to primary and secondary literature related to sanad, tahammul wa ada’ul hadis, and the phenomenon of hadith dissemination on digital platforms. The findings indicate that claims of connected sanad on social media can be justified if they fulfill the basic principles of tahammu , namely that both parties know each other and understand each other's reliability. However, strict verification mechanisms are necessary to ensure the accuracy and authenticity of hadith transmission. The implication is that social media users must be more critical in accepting sanad claims and should refer to competent hadith scholars to avoid spreading fabricated or weak hadith. This study contributes to contemporary discussions on integrating hadith transmission traditions with the advancements of digital technology.